EFEKTIVITAS PENERAPAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR IPAS MATERI WUJUD ZAT DAN PERUBAHANNYA - Sri Lestari; Yuni Ratnasari; Eka Zuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low learning outcomes of students in natural and social science subjects (IPAS) can be caused by the use of ineffective learning methods. This study aims to evaluate the effectiveness of experimental methods on the learning outcomes of IPAS on the topic of discussion of the form of substances and their changes. The research subjects consisted of 21 students who were fourth grade students of SD Negeri Mangunrejo 2. The research was designed quantitatively with a one group pretest-posttest model. The research instruments used were observation and learning outcome tests given before and after the experimental method treatment in IPAS learning. Data were analyzed using statistical tests to determine significant differences between pretest and posttest results. The average pretest result was 57.62. After the experimental method treatment in IPAS learning has increased. The average posttest score was 78.81. These results show that the experimental method is effectively able to improve student learning outcomes on the concept of the form of substances and their changes. Thus, the application of experimental methods has been effective in improving student learning outcomes in natural and social science subjects (IPAS). The experimental method is a learning method that directs students to carry out experiments independently so that students are able to experience and prove themselves about what they are learning. . In addition to improving student learning outcomes, it can also create contextual learning that is student-centered, meaningful, more active and fun.